2012
DOI: 10.1007/s10549-012-2034-4
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-30a inhibits cell migration and invasion by downregulating vimentin expression and is a potential prognostic marker in breast cancer

Abstract: Tumor recurrence and metastasis result in an unfavorable prognosis for cancer patients. Recent studies have suggested that specific microRNAs (miRNAs) may play important roles in the development of cancer cells. However, prognostic markers and the outcome prediction of the miRNA signature in breast cancer patients have not been comprehensively assessed. The aim of this study was to identify miRNA biomarkers relating to clinicopathological features and outcome of breast cancer. A miRNA microarray analysis was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
160
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(177 citation statements)
references
References 50 publications
16
160
0
1
Order By: Relevance
“…Previous studies have demonstrated that miR-30a is involved in the progression of various malignant tumors (20,21,23). However, the mechanism of miR-30a in the progression of cervical cancer remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that miR-30a is involved in the progression of various malignant tumors (20,21,23). However, the mechanism of miR-30a in the progression of cervical cancer remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that the dysregulation of miR-30a contributes to various malignant tumors, including lung, thyroid, gastric, breast and colon cancer (18)(19)(20)(21)(22)(23). miR-30a promotes tumorigenesis in these cancers by directly targeting tumor-associated proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the expression of miR30a decreases with the progression of lymphoma, leukemia, lung, ovarian, breast and colon cancer (Cheng et al, 2012;González-Gugel et al, 2013;Guan et al, 2012;Lee et al, 2012;Liu et al, 2013;Ma et al, 2012;Võsa et al, 2013), all cancers in which SIX1 overexpression has been detected (Behbakht et al, 2007;Ford et al, 1998;Mimae et al, 2012;Ono et al, 2012;Wang et al, 2011). Importantly, increased SIX1 expression enhances progression of RMS and several additional tumor types by re-activating many of the same signaling networks that SIX1 turns on developmentally to promote cell survival, proliferation and migration (Christensen et al, 2008;Khan et al, 1999;Yu et al, 2006;Yu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer and colon cancer, SIX1 induces an EMT and thereby promotes progression of these malignancies (McCoy et al, 2009;Micalizzi et al, 2009;Ono et al, 2012). Of note, miR30a has been implicated as a tumor suppressor in a variety of cancers, primarily through downregulation of EMT-driving proteins (Cheng et al, 2012;Kumarswamy et al, 2012). Given our demonstration that miR30a downregulates Six1 developmentally, and existing data that the two molecules have a reciprocal expression pattern in numerous of the same tumor types, it is tempting to speculate that miR30a loss might contribute to high Six1 expression in multiple types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…At present, >1000 miRs have been identified in the human and mouse genomes, a number of which have been found to be involved in cell migration (4,5). It has been reported that miRs, including miR-let-7a, -16, -30a, -34a, -107, -125b, -200c, -203, -218, -424 and -488, inhibit the migration of specific tumor cells and other normal cell lineages (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). However, other miRs, including miR-10b, -20, -21 and -144, have been reported to promote cell migration (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%